Dietary Fiber - Jayesh Trivedi (Global Journal of Obesity, Diabetes and Metabolic Syndrome - Peertechz Publications, 2016)
To the identification of food components that can optimize our physiological and psychological functions. This development, which aims to ensure the welfare, health and reduced susceptibility to disease during life, gave birth to the concept of "functional foods".  "Dietary fiber is the remnants of the edible part of plants and analogous carbohydrates that are resistant to digestion and absorption in the human small intestine with complete or partial fermentation in the human large intestine.